Copper Mobility Assessment Using Speciation Schemes: Case Study–Mantrijeron District, Yogyakarta, Indonesia - Phetnakhone Xaixongdeth; Heru Hendrayana; Doni Prakasa Eka Putra; Dwikorita Karnawati; Tsutomu Sato (Geological Engineering Department Universitas Gadjah Mada, 2015)
factors such physical and chemical properties, especially mineralogical composition of such environment. This study focused on the mineralogical of two soils types (fine sandy loam and loamy fine sand) to retain/mobile Cu. Two non contaminated soils from Yogyakarta urban area, Indonesia, were artificially contaminated with Cu solution. Subsequently, soils artificially contaminated were extracted from various geochemical phases of soil by sequential extraction procedure. The results show that both of soils types can retain Cu well with maximum is 5.8 mg/g of loamy fine sand and 3.9mg/g of fine sandy loam. Additionally, the iron amorphous phase content in clay fraction is influence Cu retains in these soils. This is advantage in environment of Yogyakarta urban area, Indonesia, where this area underlain by loamy sand soil. Keywords: Copper, mobility, iron, sequential extraction.